Cyclodextrin nanocarriers in Coordination Chemistry: Enhancing encapsulation and targeted delivery of 5-Fluorouracil for cancer treatment - Sara Payamifar; Amin Foroozandeh; Mehrab Pourmadadi; Majid Abdouss (Results in Chemistry)
Cancer continues to be one of the most common causes of mortality globally, claiming approximately eight million lives each year. Chemotherapy is the primary treatment protocol; however, a significant challenge is the solubility of most anticancer drugs, which adversely affect healthy tissues and hampers therapeutic efficacy. Cyclodextrin (CD) and its derivatives offer a promising solution to these limitations. Integrating nanotechnology with CDs in drug delivery systems represents a groundbreaking approach. CDs with unique structural and physicochemical features are invaluable agents that have confirmed their potential to perform numerous roles at the nanoscale level in pharmaceutical technology advancements to formulate novel drugs and enhance current formulations. The usage of CDs is not unknown, and there are multiple verified and marketed drug-CD complexes worldwide. Fluorouracil (5-FU), a widely used chemotherapeutic agent, shows efficacy against cancers such as colon, pancreas, breast, gastrointestinal tract, and ovaries. Recent advancements have demonstrated that CD-based nanotechnology systems enhance the therapeutic impact of 5-FU, promoting sustained health and prolonging the lifespan of both healthy and treated cells. This review explores the innovative application of CD nanocarrier systems for the encapsulation and targeted delivery of 5-FU in cancer treatment. It discusses the potential of these systems to improve anticancer efficacy and prevent cancer cell proliferation.In this review, CDs, as precious materials in the fields of drug delivery and medicine owing to their unique properties, are briefly described first, primarily for readers who are not very familiar with this area. Then, synthesis methods and properties of 5-FU@CD nanocarriers are explained. In the following, recently developed various β-CD NPs, β-CD NCs, β-CD NEs, and β-CD NFs used for cancer treatment are debated. Recently developed practical uses of 5-FU@CD nanocarriers are presented. Finally, recent progress in cancer treatment and antimicrobial activity are expressed.